2017
DOI: 10.1017/s0021932017000566
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Empowerment and Gender Inequality in Adolescent Nutritional Status: Evidence From the Indonesian Family Life Survey

Abstract: SummaryIn contrast to the extensive knowledge on the association between women's empowerment and the nutritional status of children under the age of five, relatively little is known about the influence of women's empowerment on adolescents' nutritional status. This study aimed to assess the association between women's empowerment and gender inequalities in adolescent nutritional status. Data were from the Indonesian Family Life Survey (IFLS) covering the period 1997 to 2015, and consisted of 16,683 observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
11
1
Order By: Relevance
“…For instance, maternal education beyond primary increased the odds of thinness in younger adolescents. Hence, while most studies have found a positive association between maternal education and especially girls' nutritional status through increased knowledge and use of health services, higher household income and increased decision-making power (Dancer & Rammohan, 2009;Aslam & Kingdon, 2012;Rahman et al, 2015;Hasan et al, 2016;Kunto & Bras, 2018), this study's findings suggest that paternal education is equally, or even more, important than maternal education. The absence of a protective effect of maternal education could be caused by women's work outside the household, thereby transferring feeding and caring tasks to others (Reed et al, 1996).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…For instance, maternal education beyond primary increased the odds of thinness in younger adolescents. Hence, while most studies have found a positive association between maternal education and especially girls' nutritional status through increased knowledge and use of health services, higher household income and increased decision-making power (Dancer & Rammohan, 2009;Aslam & Kingdon, 2012;Rahman et al, 2015;Hasan et al, 2016;Kunto & Bras, 2018), this study's findings suggest that paternal education is equally, or even more, important than maternal education. The absence of a protective effect of maternal education could be caused by women's work outside the household, thereby transferring feeding and caring tasks to others (Reed et al, 1996).…”
Section: Discussioncontrasting
confidence: 69%
“…The absence of a protective effect of maternal education could be caused by women's work outside the household, thereby transferring feeding and caring tasks to others (Reed et al, 1996). Some studies have pointed out that maternal occupation might result in less contact time including adverse child feeding and care practices (Kunto & Bras, 2018), leading to a negative effect on growth of children. Nevertheless, the present findings are in line with a recent study from Nepal that found that, while maternal secondary education or higher was a significant contributor to stunting in under-five children in 1996, it lost significance in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that girls do not cook, exposure to snack food promotion is increasing, girls are poorly informed and not concerned about good nutrition, and there are no major efforts to combat the snacking trend suggests that these eating patterns will persist, at a time when lifestyle behaviours, including eating, are established. Although the conceptual model used in this qualitative study helped to capture multiple and interacting factors influencing food choices and intake, we omitted to examine certain determinants of eating behaviours, such as household socio‐economics and mother's education, shown to be associated with nutritional status of adolescent girls in Indonesia and elsewhere (Kunto & Bras, ; Madjdian et al, ). We recognize that a wider range of potential determinants of eating patterns exist, as presented in a recently developed conceptual framework on adolescent malnutrition based on a systematic review of quantitative studies, which can be analysed through quantitative assessments (Madjdian et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, better-educated mothers might also be able to influence their children’s eating behavior more. 14,36 For this reason, we used the mother’s completed years of schooling (0-12 years) as a control variable. Third, sibling size and birth order might affect intrahousehold food distribution and interhousehold food selection.…”
Section: Methodsmentioning
confidence: 99%
“…13 The trend continues into adolescence, and, surprisingly, boys have a lower nutritional status than girls at this life stage. 13,14 During the New Order regime (1966-1998), the National Family Planning Program was established to accelerate economic growth. The program promoted the norm of the small, happy, and prosperous family.…”
Section: Introductionmentioning
confidence: 99%